Image based Ubuntu operating system using packer solutions - Elfrin Erawan; Muhammad Salman (Gema Wiralodra, 2023)
System frequent Linux operations are used on critical systems. Part systems big pay attention to safety and reliability. Ubuntu Linux is one of all Lots common Linux distributions used for system server operation. To improve security on Ubuntu Linux is required to strengthen the security system process. Strengthening security system operation is one solution for the system operation more stand to attacks and vulnerabilities. Center for Internet Security (CIS) is one caring organization for cyber security and provides benchmarks for configuration system safe Ubuntu operation. Benchmarks cover recommended settings for various component systems like file permissions, application, configuration networking, logging, and management of users. The study aims to improve security system operation with the use of control strengthening security based on CIS Benchmark v1.1.0 servers’ level 2 with the automatic model use packers application. The developed methodology consists of four phases. The first phase is Packer server installation and configuration. The second phase is to build a configuration base Ubuntu installation with user data. The third phase is the application Ansible playbook in runtime Packer automation for automation reinforcement at the time of installation and produces image virtual machine. In phase, lastly, apply structure using image virtual machine-generated and verified percentage reinforcement and optimization achieved. After strengthening security, use research methods. This generated a score conformity audit of 218 controls or 99.54% of the total 219 CIS Benchmark controls.